Optoelectronic and Photonic Characteristics of Al/p-Si Diode with Boric Acid-Doped Zinc Oxide Interlayer - Al-Sehemi, Abdullah G. G.; Tataroglu, A.; Karabulut, Abdulkerim; Dere, Aysegul; Al-Ghamdi, Ahmed A. A.; Yakuphanoğlu, Fahrettin (Springer, 2023)
Al/ZnO/p-Si diodes have been fabricated using different doping concentrations of a boric acid (H3BO3)-doped zinc oxide (ZnO) interlayer. The boric acid-doped ZnO films were obtained by the sol-gel method and coated by the spin-coating technique. The optoelectronic and electronic properties of the prepared diodes were studied under different illumination and frequency conditions. Current measurements of the diodes under both dark and illumination indicate that they exhibit a photovoltaic behavior. The diode with 5 wt.% H3BO3-doped ZnO interlayer showed the best diode properties with a rectification ratio of 4.23 x 10(4) at & PLUSMN; 5 V. Also, the photocurrent, photoconductance, and photocapacitance transients of the diodes prove that they exhibit both photodiode and photocapacitor behavior. In addition, the capacitance and conductance measurements of the diodes were carried out over a wide frequency range. The results denote that the generated diodes can be utilized as photo-diode/capacitors in optoelectronic technologies.
Keywords: Thin-Films; Electrical-Properties; Dielectric-Properties; Capacitance-Voltage; Optical-Properties; Schottky Diode; Zno; Interface; Heterostructures; Photoresponse